Assessment of Critical Resource Use in Aircraft Manufacturing - Iulia Dolganova; Vanessa Bach; Anne Rödl; Martin Kaltschmitt; Matthias Finkbeiner (Circular Economy and Sustainability, 2022)
The global aircraft fleet has been expanding worldwide, leading to a high demand for primary resources. Simultaneously, recycling initiatives for decommissioned aircraft are still incipient. Following circular economy principles, the aims of this paper are to identify potentially critical resources used and related environmental impacts, to derive recommendations regarding recycling, and to analyze the influence of increasing utilization of lightweight composite materials in aircraft manufacturing. It was identified that the engine is the structure containing resources with the highest scarcity, with tantalum dominating seven of the eleven analyzed impact categories. Aluminum, titanium, and nickel were shown to lead to the highest environmental impacts. Hotspots in the criticality and environmental assessment often occur due to alloying resources with a low mass share. It was shown that aluminum and steel alloy recycling should be prioritized. A higher lightweight composite material share in the aircraft increases impacts in the categories climate change and fossil resource depletion by 12% and 20%, respectively, whereas the impact of the category acidification, political stability, and demand growth decreases by 16%, 35%, and 60%, respectively.
Keywords: 330; Aircraft; Resources; ESSENZ; Criticality; Life cycle assessment